Organic Vegetable Business Empowerment of Hijau Daun Farmers Group, Karang Rejo, North Metro - Agus Sutanto; Hening Widowati; Nani Septiana; Achyani; Fenny Thresia; Nedi Hendri (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
he excessive use of chemicals for vegetable cultivation in Karangrejo, North Metro threatens the sustainability of agriculture. The high control of pests, weeds, and labor costs causes farmers to use chemicals and doses tend to increase, which poses a risk to consumers. PKM objectives: 1. Organic cultivation, 2. Training on post-harvest innovation on washing, packing, labeling, and packaging variations. 3. Variations of processed organic vegetables: ice cream and nuggets. 4. Development of offline and online marketing. Activities during July-September 2022, to 15 members of the Hijau Daun farmers group, with assistance/training on organic cultivation, post-harvest with the application of Pumakkal Liquid Fertilizer Production of PT. Pumahitari University of Muhammadiyah Metro, making ice cream and vegetable nuggets, offline and online sales practices. Activity results: 1. Farmer groups know and are capable of environmentally friendly organic cultivation. 2. Able to make compost and liquid fertilizer and 9 types of vegetables obtained Prima 3.3 certificate. Able to make ready-to-cook packages, Hida ice cream, and nuggets and use the web.